Measurement and Assessment of the Level of Economic Development of the Counties of the Opolskie Voivodeship - Podstawka, Marian; Suchodolski, Bartłomiej (Management and Administration Journal, 2019)
The publication presents the problems of local development on the example of counties in opolskie voivodeship. The aim of the article is an attempt to assess the level of diversification of economic development in the counties belonging to the opolskie voivodeship in 2010-2015. The evaluation of the level of counties development was carried out using Hellwig taxonomic development measure. The study confirmed the research hypothesis assuming the existence of diversification of economic development of the studied counties. The study showed the existence of a relatively constant diversification of the development of the counties in all of the analyzed years.